2014
DOI: 10.1088/2041-8205/788/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

Universality of the Near-Infrared Extinction Law Based on the Apogee Survey

Abstract: Whether the near-infrared (NIR) extinction law is universal has been a long debated topic. Based on the APOGEE H-band spectroscopic survey as a key project of SDSS-III, the intrinsic colors of a large number of giant stars are accurately determined from the stellar effective temperature. Taking this advantage and using a sample of 5942 K-type giants, the NIR extinction law is carefully re-visited. The color excess ratiorepresentative of the NIR extinction law, shows no dependence on the color excess when E(J −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 34 publications
9
95
0
Order By: Relevance
“…Several recent studies (Nishiyama et al 2009;Fitzpatrick & Massa 2009;Stead & Hoare 2009;Schödel et al 2010;Fritz et al 2011;Wang & Jiang 2014) have demonstrated such power law with exponents α ≈ 2 is suitable for the Galactic extinction in the near infrared. Since we can calculate the extinction index A K based on two different color indexes (J − K and H − K) for Mc20, we can establish α as the value that matches both extinction calculations for each star.…”
Section: Extinction and Distancementioning
confidence: 95%
“…Several recent studies (Nishiyama et al 2009;Fitzpatrick & Massa 2009;Stead & Hoare 2009;Schödel et al 2010;Fritz et al 2011;Wang & Jiang 2014) have demonstrated such power law with exponents α ≈ 2 is suitable for the Galactic extinction in the near infrared. Since we can calculate the extinction index A K based on two different color indexes (J − K and H − K) for Mc20, we can establish α as the value that matches both extinction calculations for each star.…”
Section: Extinction and Distancementioning
confidence: 95%
“…Compared to shorter (optical) and longer (MIR) wavelengths, the extinction curve is considered relatively constant in the NIR regime (e.g. Indebetouw et al 2005;Lombardi et al 2006;Román-Zúñiga et al 2007;Ascenso et al 2013;Wang & Jiang 2014) and the power-law slope of the NIR extinction curve typically only varies at a level of ∼5% (Stead & Hoare 2009;Fritz et al 2011). In very dense cores the formation of ice mantles and the grain growth could have an additional impact.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…For example, the CCM extinction curve contains no variation in the infrared, while the extinction curve of Fitzpatrick & Massa (2009) is more variable in the NIR than in the red-optical. Different authors have found both "universal" NIR extinction (e.g., Wang & Jiang 2014) and variable infrared extinction (e.g., Zasowski et al 2009). Meanwhile optical studies essentially always find extinction curve variability, though often with the caveat that "most" extinction curves are compatible with an "average" Milky Way extinction curve (e.g., Krełowski & Strobel 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the extinction curve have focused on only a small range of wavelengths for practical reasons, for example, focusing either on only the optical (e.g., Schlafly et al 2010) or only the near-infrared (NIR) (e.g., Wang & Jiang 2014) extinction curve. This means that individual parts of the extinction curve are known much better than the connections between these parts.…”
Section: Introductionmentioning
confidence: 99%